Immunogenicity of heterologous Fc and Fab immunoglobulin fragments in rabbits, guinea-pigs and rats - Binaghi, R. A. (1967)
Rabbits, guinea-pigs and rats were immunized with various heterologous 7S and 19S immunoglobulins from each other and man, and the antisera obtained were studied by immunoelectrophoresis. Rabbits produced antibodies against the Fc and the Fab fragments of the immunoglobulin injected, while guinea-pigs and rats only produced anti-Fc antibodies. The fact that guinea-pigs and rats only respond to the specific determinants of each class of immunoglobulin provides a simple method for the preparation of class-specific antisera.